2001
DOI: 10.1002/jmri.1161
|View full text |Cite
|
Sign up to set email alerts
|

In vitro validation of MR measurements of arterial pulse‐wave velocity in the presence of reflected waves

Abstract: A magnetic resonance imaging projective velocity encoding sequence was used to determine the pulse-wave velocity in an artery model. To this end, a well-defined flow phantom simulating flow propagation in large arteries was used. In order to validate the measurement method in the presence of large reflected waves, these were deliberately created in the phantom. The projective sequence was applied to two measurement sites and the wave velocity was determined from the spatial and temporal separations of the foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…The temporal resolution of 25 ms for the MRI sequence used by Groenink et al is low considering the transit time between flow waves at ascending and proximal descending aorta is in the order of 20 ms. Furthermore, they used the half-peak of the flow wave as definition of pulse wave arrival, whereas in our study the foot of the velocity wave was used, a definition that should be more robust when automated transit-time assessment is less corrupted by wave reflections and not affected by distal damping of the wave front (27). Similar to our study, Groenink et al showed that PWV of the proximal aorta was increased in MFS patients versus healthy volunteers.…”
Section: Age-related Aortic Stiffening In Marfansupporting
confidence: 62%
“…The temporal resolution of 25 ms for the MRI sequence used by Groenink et al is low considering the transit time between flow waves at ascending and proximal descending aorta is in the order of 20 ms. Furthermore, they used the half-peak of the flow wave as definition of pulse wave arrival, whereas in our study the foot of the velocity wave was used, a definition that should be more robust when automated transit-time assessment is less corrupted by wave reflections and not affected by distal damping of the wave front (27). Similar to our study, Groenink et al showed that PWV of the proximal aorta was increased in MFS patients versus healthy volunteers.…”
Section: Age-related Aortic Stiffening In Marfansupporting
confidence: 62%
“…1B) (14,18,19). The aortic path lengths between the three subsequent measurement sites were manually determined along the centerline of the aorta within the scout image by using the software package MASS (Medis, Leiden, The Netherlands) ( Fig.…”
Section: Ve Mri For Pwv Mrimentioning
confidence: 99%
“…For PWV estimation, typically transit-time methods are employed estimating temporal differences of specific features of blood flow waveforms, e.g., time from foot to foot or peak to peak, between two locations of the vessel with known distance (11-24). However, the precision of this method highly depends on the exact calculation of flow difference and distance between only two measuring points (16,25,26).Methodological improvements include a more continuous evaluation along a vessel center line and cross-correlation (XCor) analysis for the estimation of waveform delays, which improved the accuracy of PWV estimation but relied on 2D PC acquisitions in sagittal oblique slices exactly transecting the thoracic aorta (27,28). Recently, more comprehensive three-dimensional (3D) CINE techniques in combination with three-directionally encoded velocities (flow-sensitive four-dimensional [4D] MRI) have been reported that provide information on multidirectional in vivo blood flow with full volumetric coverage of the vessel of interest (29)(30)(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…For PWV estimation, typically transit-time methods are employed estimating temporal differences of specific features of blood flow waveforms, e.g., time from foot to foot or peak to peak, between two locations of the vessel with known distance (11-24). However, the precision of this method highly depends on the exact calculation of flow difference and distance between only two measuring points (16,25,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation